Nyeri Kronis Gout Arthritis Menggunakan Penerapan Kompres Hangat di Panti Werdha Damai Ranomuut - Maengga, Santiani; Karame, Verra (Yayasan Syalom Cipta Sumikolah, 2025)
The prevalence of gout disease reaches 4.75% of the 10% population. Based on data in Indonesia, it is estimated that around 2.3% of 273,879,750 people suffer from gout arthritis. Based on data from the National Centers for Health Statistics, it is estimated that 34.2% of gout arthritis cases occur in developing countries and 26.3% of gout arthritis cases in developed countries (WHO, 2019). North Sulawesi Province is the 8th province in Indonesia with the highest prevalence of joint disease at 8.35%, while for the city of Manado, the prevalence of joint disease data was 7.27%. One therapy that can be used to reduce pain in gout arthritis patients is warm water compresses. The results of a case study conducted by researchers found two nursing problems that were raised as nursing diagnoses, namely chronic pain and sleep pattern disorders, and after two days of nursing care, there were changes where the nursing problems of pain and sleep pattern disorders were resolved with complaints of pain and difficulty sleeping decreased. The provision of comprehensive nursing care can address the nursing problems experienced by clients.